Professionals and public-good capabilities - Walker, Melanie; McLean, Monica (University of the Western Cape, 2015)
Martha Nussbaum (2011) reminds us that, all over the world people are struggling for a life that is fully human - a life worthy of human dignity. Purely income-based and preference based evaluations, as Sen (1999) argues, do not adequately capture what it means for each person to have quality of life. There are other things that make life good for a person, including access to publicly provided professional services. The question then is what version of education inflects more towards the intrinsic and transformational possibilities of professional work and contributions to decent societies? This paper suggests that we need a normative approach to professional education and professionalism; it is not the case that any old version will do. We also need normative criteria to move beyond social critique and to overcome a merely defensive attitude and to give a positive definition to the potential achievements of the professions. Moreover universities are connected to society, most especially through the professionals they educate; it is reasonable in our contemporary world to educate professional graduates to be in a position to alleviate inequalities, and to have the knowledge, skills and values to be able to do so. To make this case, we draw on the human capabilities approach of Sen (1999, 2009) and Nussbaum (2000, 2011) to conceptualise professional education for the public good as an ally of the struggles of people living in poverty and experiencing inequalities, expanding the well-being of people to be and to do in ways they have reason to value – to be mobile, cared for, respected, and so on. In particular we are interested in which human capabilities and functionings are most needed for a professional practice and professionalism that can contribute to transformative social change and how professional development is enabled via pedagogical arrangements